Retrospective Study of Autologous Arteriovenous Fistula Creation as Vascular Access for Hemodialysis - Sah, Bijay; Shekhar Jaiswal, Lokesh; Kumar Gupta, Rakesh (Journal of College of Medical Sciences-Nepal, 2023)
Introduction An autologous arteriovenous fistula (AVF) creation is a common vascular procedure for hemodialysis (HD) patients. This surgical procedure aim is to design a vascular conduct that withstands hemodialysis for a durable period. However, the functional outcome of this procedure varies and depends on patients’ various predictors. Methods A retrospective observational study was carried out to evaluate the functional outcome of AVF creation at the cardiothoracic vascular surgery unit of the surgery department of B.P Koirala Institute of Health Sciences from February 2019 to February 2020. The medical file of the patients was studied, relevant data entered and analyzed in SPSS statistical software. Results There were a total of 112 autologous AVF created during the study period. The mean age of the patients was 48.66±15.64 years. There were 75(67%) males and 37(33%) females. The most common limb of fistula creation was left non-dominant upper limb 95(84.8%) and right upper limb 17(15.2%). The most common type of AVF was radiocephalic fistula 66(58.9%) and brachiocephalic fistula 46(41.1%). There were 92(82.1%) mature fistula at eight weeks follow-up. These include 54(48.2%) radiocephalic fistulas and 38(33.9%) brachiocephalic fistulas. There were 20(17.8%) delayed matured fistulas at 12 weeks (12 radiocephalic and 8 brachiocephalic AVF). Conclusions The creation of an autologous AVF for hemodialysis in the upper limb has fewer complications and the maturation of the AVF depends on the vessel’s diameter. Radio-cephalic and Brachiocephalic AVF usually matures between six to eight weeks duration